Parody and intertextuality in Enrique Jardiel Poncela’s love trilogy - Greco, Barbara (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
<!–[if gte mso 9]> 800x600 <![endif]–>SourceURL:file://localhost/Users/mcugno/Desktop/RiCOGNIZIONI%20-%201,2014%20(def%204).docParody and intertextuality in Enrique Jardiel Poncela’s love trilogy. The article analyses Enrique Jardiel Poncela’s humorous trilogy (Amor se escribe sin hache, 1928, ¡Espérame en Siberia, vida mía!, 1929, Pero…¿hubo alguna vez once mil vírgenes?, 1931) from the perspective of parody. It focuses on the technique of dehumanization in the caricatural characters and on the humoristic demystification of the literary clichés that characterize the erotic literature; moreover, it studies the intertextuality with the romantic genre ̶ “hypogenre” – and in specific texts – “hypotexts” –. Through the use of Genette, Bachtin and Segre’s theories, it examines the parody phenomenon, according to its multiple manifestations in the trilogy. Finally, the article analyses the aphoristic language and the avant-gardist typographic experimentation as important elements of Jardiel’s parodical project. <!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>